Microzonation of soil resistance using shear wave velocity (Vs) for earthquake disaster mitigation in Singaran Pati District, Bengkulu City - Dhanty Kirana, Virgie; Mase, Lindung Zalbuin; Supriani, Fepy; Misliniyati, Rena; Amri, Khairul (Teknisia, 2025)
Singaran Pati District, Bengkulu City, is located in an active subduction zone, making it prone to seismic activity. However, to date, there is no detailed microzonation map available to assess local vulnerability to earthquake shocks. This study aims to produce a microzonation map based on shear wave velocity (Vs) and Ground Amplification Factor (GAF) parameters as indicators of soil resistance. Vs values are calculated sequentially at depths of Vs10, Vs20, Vs30, Vs40, and Vs50 using spectral inversion methods. Soil site classification is based on NEHRP standards. Spatial interpolation uses the Inverse Distance Weighting (IDW) method to map parameter distribution. Results show that Vs velocity increases with depth, with a dominance of Class D sites (moderate soil), followed by Class C (very dense soil and soft rock), and a small portion of Class B (moderate rock). The GAF map identifies points with the highest amplification that are at high risk of damage due to earthquakes. The maximum Ground Amplification Factor (GAF) value is shown in red on the map, with a value of 2.0, while the minimum value is shown in green, representing a value of 1.0. This condition indicates that some areas in Singaran Pati Subdistrict have a significant potential for earthquake impact. Therefore, the use of microzonation maps is crucial as a basis for structural building planning and seismic risk mitigation in the Singaran Pati area.